A disposable gold-cellulose nanofibril platform for SERS mapping. Issue 24 (11th June 2020) - Tanis, Saliha Nur; Ilhan, Hasan; Guven, Burcu; Tayyarcan, Emine Kubra; Ciftci, Hakan; Saglam, Necdet; Hakki Boyaci, Ismail; Tamer, Ugur
Abstract : In this study, we present a disposable and inexpensive paper-like gold nanoparticle-embedded cellulose nanofibril substrate for the rapid enumeration of Escherichia coli ( E. coli ) using surface-enhanced Raman scattering (SERS) mapping. Abstract : In this study, we present a disposable and inexpensive paper-like gold nanoparticle-embedded cellulose nanofibril substrate for the rapid enumeration of Escherichia coli ( E. coli ) using surface-enhanced Raman scattering (SERS) mapping. A disposable SERS substrate was simply constructed by mixing CNF and gold chloride solution at 120 °C in a water bath. The application of the resulting substrate was carried out by enrichment and SERS detection of E. coli . To this end, the spherical gold nanoparticle-embedded cellulose nanofibril substrate was used as a scavenger for E. coli . After the target bacteria E. coli were separated from the matrix via oriented antibodies, the sandwich assay procedure was carried out using 5, 5-dithiobis-(2-nitrobenzoic acid) (DTNB)-coated Au nanorod particles that acted as SERS mapping probes. The distribution density of DTNB was demonstrated visually using SERS mapping, and the assay was completed in one hour. The correlation between the E. coli and SERS mapping signals was found to be linear within the range of 15 cfu mL −1 to 1.5 × 10 5 cfu mL −1 . The limit of detection for the SERS mapping assay was determined to be 2 cfu mL −1 . The selectivity of the developed method was examined with Micrococcus luteus ( M. luteus ), Bacillus subtilis ( B. subtilis ), and Enterobacter aerogenes ( E. aerogenes ), which did not produce any significant response. Furthermore, the developed method was evaluated for detecting E. coli in artificially contaminated samples, and the results were compared with those of the plate-counting method.